THE RELATIONSHIP BETWEEN MOTHER ROLE OF MEET THE ORAL HYGIENE AND DENTAL CARIES IN PRESCHOOL CHILD IN KINDERGARTEN KUSUMA MULIA XVIII SUMBERBENDO PARE KEDIRI - Laviana Nita Ludyanti; Ari Widiyanto (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2017)
The mother's role in the meet of oral hygiene is very important to reduce the occurrence of dental caries in preschools children. Preschoolers has low personals hygiene and still in the developmental process. The aimed of this research was to determine the context of the mother's role in the meet of oral hygiene with the incidence of dental caries in preschools children 4 - 6 years old at kindergarten of Kusuma Mulia XVIII Sumberbendo Pare Kediri. The research methods used correlational design with a retrospective approach. Purposive sampling was used to obtain 26 samples of mothers who eligible as inclusion criteria. Measuring tool used a questionnaire to the mother's role in the meet of oral hygiene and observation for occurrence of dental caries in preschool children, then its analyzed by spearman rho. The result of the research showed that (76, 9%) mothers has role in the meet of oral hygiene that was in sufficient category. Whereas (80, 8%) the children had medium category. The results after the calculation using the Spearman rho test indicated for correlation coefisien = -0,515 and p value = 0,007 that means the associationÂ between mother's role in the meet of oral hygiene with the incidence of dental caries in preschools children. Reducing the incidence of dental caries is not only depend on the mother's role toward meet of oral hygiene, but also to the other factors such as food, micro-organisms, bad habits of the children in keeping oral dental hygiene and mouth, tooth brushing pattern, the shape of the teeth, and history of children's milk when as a baby which causes the dental caries.